Pengaruh Learning Cycle dengan Pendekatan Contextual Teaching Learning terhadap Keterampilan Berpikir Kritis pada Pembelajaran Sains - Ekawati, Ratna; Widiasih, Widiasih; Mashfufah, Aynin; Rufiana, Intan Sari (Universitas Nusantara PGRI Kediri, 2024)
Science learning aims to study natural phenomena systematically, involving high-level manipulative thinking processes to give physical meaning to natural phenomena around us. The main problem in science learning is students memorize science concepts, they need to be trained to solve problems and interpret natural phenomena in everyday life. One learning approach to solving problems is the Contextual Teaching and Learning (CTL) approach with the Learning Cycle strategy. The research objective is to determine the effect of the Learning Cycle with the Contextual Teaching and Learning Approach on critical thinking skills in science learning. This research uses a quasi-research method with two experimental classes. The sampling technique is cluster random sampling. The research sample was two classes in a state school in Yogyakarta. Data analysis includes the data description stage, analysis prerequisite testing stage, and hypothesis testing stage. The research results show differences in the average critical thinking skills of the Learning Cycle strategy with the CTL approach and laboratory work..